Treatment of Coexisting Chronic Neutrophilic Leukemia and Light Chain Multiple Myeloma with Hydroxyurea, Bortezomib, and Dexamethasone - Evelyn Taiwo; Huiying Wang; Robert Lewis (Case Reports in Hematology)
A 63-year-old female was incidentally found to have leukocytosis and referred to the hematology service for evaluation. Complete blood count (CBC) revealed neutrophilia with band predominance and mild thrombocytopenia. Peripheral blood flow cytometry was unremarkable without any evidence of lymphoproliferative disorder or myeloblasts. Bone marrow aspiration and biopsy revealed a markedly hypercellular marrow with myeloid lineage predominance and approximately 10% plasma cells. The monoclonal gammopathy was determined as lambda light chain with a kappa/lambda ratio of 0.06. Cytogenetics revealed normal karyotype, JAK2 kinase was negative, and rearrangement of BCR-ABL1, PDGFRA, PDGFRB, and FGFR1 was negative. The patient was diagnosed with chronic neutrophilic leukemia (CNL) associated with light chain multiple myeloma, complicated by a subdural hemorrhage. She was treated with hydroxyurea and bortezomib/dexamethasone and had complete response with normalization of CBC and kappa/lambda ratio. To the best of our knowledge, we report the first case of chronic neutrophilic leukemia and multiple myeloma treated with bortezomib/dexamethasone.